To Evaluate the Haematological Changes at Different Trimesters during Pregnancy in Tertiary Care Centre - M, Giriharan; Caroline P, Annie; P, Vaishnavi; Krishan Kumar, Dharman; T, Akash (Journal of Neonatal Surgery, 2025)
Background: Pregnancy is the term used to describe the period in which a fetus develops inside a women’s womb or uterus. Pregnancy usually lasts about 40 weeks, or just over 9 months, as measured from the last menstrual period to delivery. During pregnancy, the pregnant mother undergoes significant anatomical and physiological changes including alterations in hematologic parameters in order to nurture and accommodate the developing foetus. Aim:To assess the haematological changes at different trimesters during pregnancy. Material & Method: Blood sample reports were taken from 150 pregnant women after taking informed consent that came for regular check-up. We have collected the CBC report from the patient and taken the haematological profile such as RBC, PCV, Hb and HCT parameters at different trimesters and includes socio-demographic parameters such as height, weight were measured and age, occupation, physical activity were noted. Result: RBC’S mean value was 4.0979 ±0.54428, PCV mean value was 33.650 ±4.2068,Hb mean value was 11.189 ±1.5316, HCT mean value was 33.7390 ±3.94516. While comparing the haematological profile of different trimesters, We observed that haematological change occurred in all three trimesters ,RBC count decreased in 2nd trimester, PCV progressively decreased from 1st to 3rd trimester, Hb showed slightly changes in 2nd and 3rd trimester and HCT slightly decreased in 2nd trimester Conclusion:This study concluded that pregnancy in women alters haematological indices such as packed cell volume, haemoglobin concentration, red blood cell count shows statistical decrease in 2nd trimester because of expansion of plasma volume,increased secretion of aldosterone production by renin-angiotensin system stimulation & nutritional deficiency of iron supply. RBC count decreased in 2nd trimester and the p value of RBC (0.000) shows statistically significant while packed cell volume decreased from 1st trimester till 3rd trimester and the p value of PCV and HB is not less than 0.05 which is not considered as statistical significant.